Leadership Strategies in Diverse Intake Environments - Brit Bolken Ballangrud; Jan-Merok Paulsen (Nordic Journal of Comparative and International Education, 2018)
The case study subjected in this paper was designed to illuminate how school leadership strategies and interventions mediate external demands, in the form of the academic press, for raised outcomes, imposed from the policy environment on a school with a heterogeneous pupil population. The Norwegian research site is situated in a demographic environment of low pupil socioeconomic status, a group of factors that in other systems predicts 60%—70% of academic achievement. More specifically, the intake environment in which the school is situated is characterized by high ethnic heterogeneity and, for some parts, low scores on parents’ social welfare indicators. Data was collected from a school characterized as low performing, defined by pupil achievement on national tests, yet these outcomes had been progressing over time. Find-ings are based on observations as well as interviews with school leaders, teachers, the superintendent in the municipality, and pupils, together with a pupil survey. The paper analyzes various leadership strategies and interventions as mediating functions between the external academic press from the school district level and the internal cultural context of the school. Specifically, the findings suggest that building a core culture of inclusive ethos for all pupils, paired with pedagogical collaboration, and democratic and servant leadership, are important devices for mastering this form of diversity. The leadership practices and collaborative focus were furthermore anchored in a systemic and more integrative school organization that purposefully com-bined hierarchical structure with horizontal elements in a matrix-like design.